Thymic alterations resulting from experimental visceral leishmaniasis in a Syrian hamster (Mesocricetus auratus) - Março, Karen Santos [UNESP]; da Silva Borégio, Jaqueline [UNESP]; Jussiani, Giulia Gonçalves [UNESP]; de Souza Ferreira, Laura Flávia Esperança [UNESP]; Flores, Gabriela Venicia Araujo; Pacheco, Carmen Maria Sandoval; Laurenti, Marcia Dalastra; Machado, Gisele Fabrino [UNESP] (Elsevier, 2023)
Background: The thymus is a lymphoid organ responsible for the development and maturation of T cells, which are part of the Th1, Th2, Th17, and Treg immune responses triggered by visceral leishmaniasis. The maturation and immunological development of T lymphocytes require a bidirectional interaction between the thymic microenvironment of epithelial cells, dendritic cells, and macrophages and the extracellular matrix with differentiating lymphocytes. Objectives: We evaluated the morphological characteristics and tissue distribution of hematopoietic and stromal cells in the thymuses of hamsters experimentally infected with Leishmania infantum, aiming to gain an insight into the pathophysiology of the disease. Methods: Fifteen hamsters were subjected to intraperitoneal experimental infection with 107 L. infantum promastigotes (MHOM/BR/1972/BH46). The animals were divided into three groups, each comprising five infected hamsters, and were then euthanized 15, 60, and 120 days postinfection. The control groups consisted of three groups of five healthy hamsters euthanized simultaneously with the infected ones. Thymic morphology was evaluated through histopathology and the cell composition through immunohistochemistry. We used antibodies to mark mesenchymal cells (anti-vimentin), epithelial cells (anti-cytokeratin), macrophages (anti-MAC387), B lymphocytes (anti-CD79a), and T lymphocytes (anti-CD3). Immunohistochemistry was also used to mark the parasite in the thymus. Results: Infected and control hamsters showed no difference in thymic morphology and degree of atrophy. After 15 days of infection, CD3 + T lymphocytes in the thymus showed an increase that stabilized over time. At 120 days of infection, we detected a significant decrease in CD79a+ B lymphocytes. The parasite was present in the medullary and corticomedullary regions of 9 out of 15 hamsters. These findings confirm that the presence of a parasite can cause changes in a thymus cell population. However, further studies are needed to evaluate these changes’ effects on the immune response of infected animals.
Keywords: Histopathological changes; Immunohistochemistry; Leishmaniasis; Thymus